Penghasilan abu sekam padi menggunakan relau terubahsuai UKM - M. Faizal,; Ade Ilham,; Muhammad Fauzi Mohd Zain, (2002)
The quality of rice husk ash, which is produced using specially designed furnace at Universiti Kebangsaan is studied. By using appropriate combustion technique, high content of silica ash was able to be produced. The furnace was fabricated and improved based on the previous concept adopted by Universiti Sains Malaysia and Asian Institute of Technology. Investigation is done to determine the physical and chemical properties including temperature distribution, particle size, crystallization phase and chemical composition. It was found that the specially designed furnace was able to produce a high quality of rice husk ash